Attention to Oneself in an Apologetic Perspective: The Reception of Ancient Philosophical Practices in St. Basil the Great - Ioannis Kaminis (Communio Viatorum)
The purpose of this article is to present Saint Basil’s utilization of the philosophical heritage along with the ancient Greek literature for the benefit of Christianity. Saint Basil’s approach was influenced by a lineage of Christian philosophers, including the St. Justin the Philosopher, Origen, St. Gregory Thaumaturgus and his grandmother St. Macrina the Elder. Initially, early Christians like St. Justin the Philosopher and Clement of Alexandria portrayed Christianity as the true philosophy and the culmination of knowledge in antiquity. Then Origen employed more philosophical methods and practices in his Christian educational program. St. Basil followed this tradition, but infused his teaching with a holistic Christian interpretation. For instance, he emphasized attention to oneself in a Christian perspective. Additionally, his Address to the Young: On how they might derive benefit from Greek literature demonstrates Christianity’s capacity to assimilate and embrace other traditions while interpreting them in a manner that promotes virtue, the moral development of human being and devotion to Christ.